2014
DOI: 10.1021/ja412715m
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach to Mechanically Planar Chiral Rotaxanes

Abstract: We describe the first method for production of mechanically planar chiral rotaxanes in excellent enantiopurity without the use of chiral separation techniques and, for the first time, unambiguously assign the absolute stereochemistry of the products. This proof-of-concept study, which employs a chiral pool sugar as the source of asymmetry and a high-yielding active template reaction for mechanical bond formation, finally opens the door to detailed investigation of these challenging targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
109
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 49 publications
1
109
0
1
Order By: Relevance
“…Pillar [5]arenes have been introduced by Ogoshi and co-workers. [9] These macrocyclic compounds are easily affordable and are therefore particularly interesting buildingb locks fort he synthesis of [2]rotaxanes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pillar [5]arenes have been introduced by Ogoshi and co-workers. [9] These macrocyclic compounds are easily affordable and are therefore particularly interesting buildingb locks fort he synthesis of [2]rotaxanes.…”
Section: Resultsmentioning
confidence: 99%
“…[2,3] In this case, as ingle synthetic intermediate has to be prepared efficiently and its furtherc hemical transformationc an in principle give easy access to all kinds of functionalized [ 2]rotaxanes.H owever, this approachh as rarely been used ando nly af ew examples have been reported in the literatures of ar. [4][5][6][7][8] Stoddarth as shown that stoppere xchange can be efficientlya chieved by reactiono far otaxane bearing a phosphoniums alt stopperw ith an aldehyde under Wittig con- ditions. [4] Other examples are based on the reaction of an Oacylisourea rotaxanei ntermediate with amines [6] or on the modification of arotaxane incorporating acinnamyl ester stopper with ab ulky malonate ester by ap alladium-catalyzed Ts uji-Trost allylation reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014 we reported that, by including a covalent point stereogenic unit in the axle of a crowded rotaxane, the mechanical epimers of the product could be separated using flash chromatography 17. The separated diastereomers were then converted to enantiopure MPC rotaxanes by removing the covalent stereogenic unit.…”
mentioning
confidence: 99%
“…We previously reported that an active template18 Cu‐mediated alkyne–azide cycloaddition19 (AT‐CuAAC)20 reaction between small bipyridine macrocycle 1 ,21 alkyne 2 a and chiral azide ( d )‐ 3 a gave the rotaxane product as an equimolar mixture of mechanical epimers (Table 1, entry 1) and that variation of reaction conditions failed to impart diastereoselectivity 17, 22. We hypothesized that placing the stereochemical information on the alkyne component might lead to selectivity in the formation of diastereomeric Cu I ‐acetylide/macrocycle complexes in a biased pre‐equilibrium 23, 24.…”
mentioning
confidence: 99%